‘A MULTICULTURAL SOCIETY, IF YOU CAN KEEP IT’ Building Canadian National Identity, 1970-2010 - Titus, Samuel (Université d'Ottawa | University of Ottawa, 2020)
Much has been written on Canada’s woes at articulating a useable, broadly accepted national identity and the assorted public policy dilemmas that arise from this lack of uniting principles. Part of this stems from the residual influence of both external powers on Canadian social and political life, as well as from unanswered questions relating to domestic sovereignty and political cohesion. Accordingly, Canada’s elite and mass cultures have had a difficult time outlining a positive sketch of what it means “to be Canadian”. At best, many simply point to what Canada is not, which is woefully inadequate as a statement of national identity. During the roughly century and a half since formalizing the Dominion of Canada, numerous efforts have been made at creating and fostering a sense of national self-consciousness, but few of these have managed to stick in the minds of citizens or stand up to scrutiny and skepticism. However, perhaps the only identity that has endured is the notion that Canada is, fundamentally, a proudly multicultural state. With the rise of right wing, populist politics, both abroad and at home, and mounting anxieties over the continued existence of the liberal international order, the dominance of multiculturalism as a guiding framework is being challenged. This, therefore, raises the question: if multiculturalism can be so easily toppled, was it ever truly a central tenant of the Canadian national project?